2023
DOI: 10.32942/x2c01d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of helping on helper life-history and fitness in a cooperatively breeding bird

Abstract: Cooperative breeding occurs when helpers provide alloparental care to the offspring of a breeding pair. One hypothesis of why helping occurs is that helpers gain valuable experience (skills) that may increase their own future reproductive success. However, research typically focuses on the effect of helping on short-term measures of reproductive success. Fewer studies have considered how helping affects long-term fitness measures. Here, we analyse how helping experience affects key breeding and fitness-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This hypothesis could be relevant to sparrow-weavers as dominant females feed offspring at higher rates than dominant males (Walker et al 2021). However, compelling evidence that helping improves parenting skills remains elusive (Chesterton et al 2023;Cockburn 1998), and as immigrant subordinate sparrow-weavers rarely help at all (Walker et al 2021), it seems unlikely that direct benefits arising via skills acquisition are a major driver of helping in this system. It has also been suggested that the sex that shows higher variance in lifetime reproductive success (LRS) may invest more in helping given its lower chance of securing direct fitness by breeding (Cockburn 1998;Koenig et al 1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis could be relevant to sparrow-weavers as dominant females feed offspring at higher rates than dominant males (Walker et al 2021). However, compelling evidence that helping improves parenting skills remains elusive (Chesterton et al 2023;Cockburn 1998), and as immigrant subordinate sparrow-weavers rarely help at all (Walker et al 2021), it seems unlikely that direct benefits arising via skills acquisition are a major driver of helping in this system. It has also been suggested that the sex that shows higher variance in lifetime reproductive success (LRS) may invest more in helping given its lower chance of securing direct fitness by breeding (Cockburn 1998;Koenig et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…2021). However, compelling evidence that helping improves parenting skills remains elusive (Chesterton et al . 2023; Cockburn 1998), and as immigrant subordinate sparrow-weavers rarely help at all (Walker et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation